2022
DOI: 10.31937/ti.v13i2.1854
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation for Classification of News Categories Using Support Vector Machine Algorithm with SVD

Abstract: Online news is a digital information media currently has a very easy and flexible updating process. The News Document grouping process is implemented in several stages, including Text Mining which includes Text Pre-processing which includes Tokenizing, Stopword removal, Stemming, Word Merging, TF-IDF and Confusion Matrix. Of the several techniques in Text Mining, the most frequently used for News Document classification is the Support Vector Machine (SVM). SVM has the advantage of being able to identify separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
0
0
Order By: Relevance
“…It is necessary to say when trained SVD and then K-means are used together or just K-means and elbow method are used in the algorithm they give closer numbers to WOS results but since the labels should be clear up to the sub-categories, it was not preferred. Since a study showed that a combination of SVD and SVM algorithms gave better accuracy when used together than just SVM used itself, we preferred a similar way as in their work by employing the favors of SVD by dimension reduction (., & Rarasati , 2022). When using the data tables for both training and testing, we employed the same index terms for training as the same as in the WOS search.…”
Section: Methodsmentioning
confidence: 99%
“…It is necessary to say when trained SVD and then K-means are used together or just K-means and elbow method are used in the algorithm they give closer numbers to WOS results but since the labels should be clear up to the sub-categories, it was not preferred. Since a study showed that a combination of SVD and SVM algorithms gave better accuracy when used together than just SVM used itself, we preferred a similar way as in their work by employing the favors of SVD by dimension reduction (., & Rarasati , 2022). When using the data tables for both training and testing, we employed the same index terms for training as the same as in the WOS search.…”
Section: Methodsmentioning
confidence: 99%